answersLogoWhite

0


Best Answer

x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.

User Avatar

Wiki User

โˆ™ 2015-01-12 02:16:22
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.81
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1765 Reviews

Add your answer:

Earn +20 pts
Q: How do you solve x2 plus 3x plus 3 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you solve for x X2 plus 3x plus 1 equals 0?

x2+3x+1 = 0 Using the quadratic equation formula gives you: (x+2.618033989)(x+0.3819660113) = 0 So: x = -2.618033989 or x = -0.3819660113


X2 plus 3x plus 7 equals 5?

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}


Can you put the equation x2 - 5 -4x2 plus 3x equals 0 in the form ax2 plus bx plus c equals 0?

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0


X2 plus 3x plus 10 equals 0?

-2


What is the GCF of x2 plus 3x equals 0?

X2 + 3X = 0X(X + 3) = 0--------------------X is the greatest common factorso,X = 0----------orX = - 3----------- assuming you might want to solve this type of problem some day


Would x2 plus 3x plus 2 equals 30 be considered a quadratic equation although 'y' doesn't equal '0'?

Yes:- x2+3x+2 = 30 X2+3x+2-30 = 0 x2+3x-28 = 0 (x-4)(x+7) = 0 x = 4 or x = -7


Solve the quadratic equation using factoring x2 3x 2 0?

x2+3x+2=0 (x+2)(x+1)=0 x=-2 or -1


X2 plus 3px plus p equals 0 what is p?

x2 + 3px + p = 0 x2 + p(3x + 1) = 0 p(3x+1) = -x2 p = -x2/(3x+1) So p can have any value at all. In fact, around x = -1/3, p goes asymptotically to + and - infinity.


X2 plus 3x - 18 equals 0?

x^2+3x-18=0 (x+6)(x-3)=0


How do you factor x2 plus 3x-4 plus 0?

(x-1)(x+4)


X2 plus 3x-7 equals 5x plus 8?

x2 + 3x - 7 = 5x + 8; thus, x2 + 3x - 7 - 5x - 8 = x2 - 2x - 15 = (x - 5)(x + 3) = 0. Therefore the solution is x = 5 or -3.


Can you complete the square factor and use the quadratic formula to solve these two equations x2-4x-21 equals 0 and x2-3x-18 equals 0?

x2-4x-21 = 0 => x = -3 or x = 7 x2-3x-18 = 0 => x = -3 or x = 6

People also asked